Cardiology Research Institute, Tomsk National Research Medical Center - E. V. Grakova; K. V. Kopyeva; A. T. Teplyakov; L. K. Isakov; M. N. Sinkova; N. I. Tarasov (Российский кардиологический журнал)
Aim. To assess the prognostic role of cardiac biomarkers (galectin-3, soluble ST2 (sST2), and N-terminal pro-brain natriuretic peptide (NT-proBNP)) in risk stratification of adverse cardiovascular events (CVEs) in patients with heart failure (HF) after implantation of an automatic implantable cardioverter-defibrillator (AICD) within 12-month follow-up period.Material and methods. The study included 57 patients (men, 41; mean age, 65 (59; 68) years) with coronary artery disease and NYHA class II-III HF with left ventricular ejection fraction of 34 [26; 40]%. All patients were implanted with AICD. Serum levels of NT-proBNP, sST2, and galectin-3 were determined by enzyme immunoassay prior to AICD implantation.Results. It has been established that in order to stratify the risk of unfavorable HF in patients after AICD implantation for 12-month follow-up, all three studied biomarkers can be considered as prognostic factors. Thus, an increase in the level of NT-proBNP ≥1046,6 pg/ml (AUC=0,68; p=0,009), sST2 ≥34,43 ng/ml (AUC=0,78; p<0,0001) and galectin-3 ≥11,6 ng/l (AUC=0,72; p=0,0014) predicts a high risk of adverse CVEs. The combination of sST2 and galectin-3 increased the predictive value of the analysis (AUC=0,84; p<0,0001), while the addition of NTproBNP did not increase the accuracy of risk stratification.Conclusion. The determination of the combination of galectin-3 and sST2 can potentially help identify a group of patients with HF after AICD implantation with a high risk of adverse CVEs for intensification and optimization of treatment.